Penerapan Metode Dijkstra Pada Jalur Distribusi LPG Untuk Penentuan Jarak Terpendek - Adi, Novi Hendri; Giatman, Muhammad; Simatupang, Wakhinuddin; Afrina, Afrina; Watrianthos, Ronal (Building of Informatics, Technology and Science (BITS), 2021)
Determining a shortest path is a crucial and necessary thing in connection with optimizing the time used and some savings in other fields. This research aims to design a software for determining the shortest distance on a web-based LPG gas distribution line by applying the Dijkstra solving procedure at PT. Amartha Anugrah Mandiri. This study uses the SDLC (software development life cycle) development method using waterfall modeling, to determine the closest route during the distribution of LPG gas using the Dijkstra solution procedure, namely by determining which location is used as the initial node, then set the distance value at the initial node to neighboring nodes. the closest one by one. The results of this study make it easier for drivers to find the closest route that can be passed to the base location. Dijkstra's solving procedure in the software for determining the shortest distance in the PT. Amartha Anugrah Mandiri can form the shortest distance traveled to get to the base